Kaia and the bees [book with audioplayer] - Boelts, Maribeth, 1964- (Findaway World, LLC, 2020)
"Kaia is the brave type. Like hottest-hot-pepper brave. But there is one thing that scares her: BEES! And right now, thousands of bees live on her roof because Kaia's dad is a beekeeper. Her dad says that the world needs bees and that's why they are beekeepers. But only he goes on the roof, not Kaia - unless she can find a way to be the brave girl she always says she is. Against a sunny city setting, author Maribeth Boelts and illustrator Angela Dominguez depict Kaia's small courageous steps - and her tiny insect neighbors - with great empathy and charm. Buzzing with storytime potential, Kaia and the Bees is an honest and relatable tale about bravery and compassion, as well as the importance of bees to our world."--